Distinctive Competency and its Implication to Marketers in Ghana - Erastus Yamoah, Emmanuel; (Candidate), PhD (British Journal of Marketing Studies, 2013)
For a business to develop and sustain a competitive advantage, it must have some sort of competitive advantage, based on a distinctive competency, which enables it to produce a unique value proposition. A distinctive competency is a competency that is maintainable in the face of competition. It is not imitable, at least for a while. This paper reviews the concept of distinctive competency and its implication to marketers in Ghana. The paper concludes that identifying key internal strengths that meets the needs and expectations of customers and taking advantage is essential to success in the marketplace.